Selective and consistent news avoidance in Aotearoa New Zealand: motivations and demographic influences - Alex Beattie; John Kerr; Richard Arnold (Kōtuitui)
This study explores selective and consistent news avoidance in Aotearoa New Zealand. Existing research suggests that selective news avoidance rates are high in Aotearoa New Zealand (Myllylahti M, Treadwell G. 2023. Trust in News in Aotearoa New Zealand 2023. Journalism, Media and Democracy: AUT Research Centre for Journalism, Media & Democracy., Myllylahti M, Treadwell G. 2024. Trust in News in Aotearoa New Zealand 2023. Journalism, Media and Democracy: AUT Research Centre for Journalism, Media & Democracy.) but we know little about why this is and if reasons for avoiding the news differ depending on the type of news consumer. Drawing from a nationally representative survey of 1204 participants, this study explores the relationships between news avoidance, motivations and demographic factors. We confirm the high rates of selective news avoidance and report that Aotearoa New Zealand has high rates of consistent news avoiders. New Zealanders’ primary motivations to avoid the news are because of how the news negatively affects their well-being, or because they do not trust the news, or are turned off by the quality of news reporting. We also find that gender and political beliefs are associated with the frequency of and motivations for news avoidance. We discuss why New Zealand has high rates of selective and consistent news avoidance, as well as the implications, and furthermore why women, and people with very left-wing or very right-wing political beliefs may avoid the news more frequently than other groups.